PWI DI KOTA JAMBI 1963-1974 - Rohmo Reiyanto Pinayungan (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2019)
AbstractPWI Jambi City is one of the organizations formed to provide services in the form of information in the mass media. Journalists are an important part of PWI's existence which can make important contributions to the development of information in the community in Jambi. The research in this paper aims to explain the history and development of the Jambi City PWI from 1963-1974 and the role of the Jambi City PWI. The research method used is the historical method, including heuristic stages, source criticism, interpretation, and historiography. Data sources were obtained from books and archives relating to PWI Jambi City, as well as interviews with management who were directly involved in the PWI of Jambi City. In this study using system theory in which system theory provides a very strong description model of organizational processes. The results showed that the PWI in Jambi City was formed based on the wishes and initiative of local Jambi journalists. Long before the formation of PWI in Jambi City, a local Jambi journalist organization or organization called IWD (Djambi Journalists Association) was formed. The role of PWI in providing mass media services can be seen from the activities in providing all public information descriptions. While its role is in providing protection for journalists who are members of it, PWI in Jambi City provides assistance and legal protection for journalists who are members of PWI.Keywords: Journalists, Indonesian Journalists Association, Press, Mass Media AbstrakPWI Kota Jambi merupakan salah satu organisasi yang dibentuk untuk memberikan jasa berupa informasi dalam media massa. Wartawan menjadi bagian penting dari keberadaan PWI yang dapat memberikan kontribusi penting bagi perkembangan informasi di masyarakat di Jambi. Penelitian dalam tulisan ini bertujuan untuk menjelaskan sejarah dan perkembangan PWI Kota Jambi dari tahun 1963-1974 serta peranan PWI Kota Jambi. Metode penelitian yang digunakan adalah metode sejarah, meliputi tahapan heuristik, kritik sumber, interpretasi, dan historiografi. Sumber data didapat dari buku-buku dan arsip yang berkaitan dengan PWI Kota Jambi, serta wawancara dengan pengurus yang terlibat langsung dalam PWI Kota Jambi. Di dalam penelitian ini menggunakan teori sistem yang di mana teori sistem memberikan suatu model deskripsi yang sangat kuat mengenai proses organisasi. Hasil penelitian menunjukkan bahwa PWI di Kota Jambi terbentuk atas keinginan dan inisiatif wartawan lokal Jambi. Jauh sebelum terbentuknya PWI di Kota Jambi, telah terbentuk lembaga atau organisasi kewartawanan lokal Jambi yang bernama IWD (Ikatan Wartawan Djambi). Peranan PWI dalam memberikan pelayanan media massa terlihat dari kegiatan dalam memberikan semua uraian informasi publik. Sedangkan peranannya dalam memberikan perlindungan terhadap wartawan yang tergabung didalamnya, PWI di Kota Jambi memberikan bantuan dan perlindungan hukum terhadap para wartawan-wartawan yang tergabung didalam PWI.Kata Kunci : Wartawan, Persatuan Wartawan Indonesia, Pers, Media Massa